2010
DOI: 10.1021/ac902923s
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative High-Performance Liquid Chromatography−Electrospray Ionization Tandem Mass Spectrometry Analysis of Bis-N7-Guanine DNA−DNA Cross-Links in White Blood Cells of Cancer Patients Receiving Cyclophosphamide Therapy

Abstract: Cyclophosphamide (CPA) is a DNA alkylating agent widely used in cancer chemotherapy. CPA undergoes metabolic activation to phosphoramide mustard and nornitrogen mustard (NOR) which alkylate the N-7 position of guanine in DNA to produce N-[2-(N7-guaninyl) ethyl]-N-[2-hydroxyethyl]-amine (G-NOR-OH) monoadducts and N,N-bis[2-(N7-guaninyl) ethyl] amine cross-links (G-NOR-G). G-NOR-G cross-links are strongly cytotoxic and are thought to be responsible for the biological activity of CPA. In the present work, an isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 24 publications
1
51
0
Order By: Relevance
“…18, 20, 49-52, 56, 59, 64 Recently, tandem mass spectrometry with stable isotope dilution has been employed to identify and quantitate some of these DNA adducts. 53, 54, 61-63 Collectively, the studies indicate that these electrophiles react predominantly at the N7 atom of dG, although N3-dA modification can also be significant. 66 The toxicity of mustard agents has been attributed to interstrand DNA cross-links.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…18, 20, 49-52, 56, 59, 64 Recently, tandem mass spectrometry with stable isotope dilution has been employed to identify and quantitate some of these DNA adducts. 53, 54, 61-63 Collectively, the studies indicate that these electrophiles react predominantly at the N7 atom of dG, although N3-dA modification can also be significant. 66 The toxicity of mustard agents has been attributed to interstrand DNA cross-links.…”
Section: Discussionmentioning
confidence: 90%
“…One study reported the identification of bis-N7-guanine cross-links in white blood cells of cancer patients receiving cyclophosphamide therapy, 53 and sulfur mustard (bis-(2-chloroethyl)-sulfide, SM) also forms bis[2-(guanin-7-yl)ethyl]sulfide cross-links in tissues of rodents, and urine of rabbits exposed to SM. 62, 63 The potential formation of ring-opened FapyG adducts was not addressed in those studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data reveal that alkylating agents and bleomycin directly damage telomeres. Telomeres and the Terc gene may be at increased risk of the damage induced by alkylating agents, such as guanine DNA-DNA cross-links, because of their G-rich DNA sequences [39,40]. Although the target of bleomycin is still unclear, there is evidence that bleomycin treatment can induce DNA damage to the telomere region [15,36].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 5.18 shows the scores plot of live cells treated with an anticancer drug, cyclophosphamide monohydrate, and an untreated control group of cells. Cyclophosphamide monohydrate is an alkylating agent that acts on DNA at the seventh position of nitrogen in guanine bases [70][71][72] mutations [70][71][72][73][74]. It is a common chemotherapeutic in the treatment of various cancers [73,74].…”
Section: Scp Of Live Cells In Aqueous Environmentmentioning
confidence: 99%